Respuesta :

(a) We use the given g(x) to find the values

g(-1), Here x = -1 which is x<=-2

so we use g(x) = [tex]\frac{1}{4} x - 1[/tex]

Plug in -1 for x

so g(-1) =  [tex]\frac{1}{4}(-1) - 1[/tex]=  [tex]\frac{-1}{4} - 1[/tex]=  [tex]\frac{-5}{4}[/tex]

g(-1) =  [tex]\frac{-5}{4}[/tex]

(b) g(1), Here x=1  and it comes under the interval x>=1

so we use g(x) = -2

g(1) = -2

(c) g(4), Here x=4  and it comes under the interval x>=1 because 4 is greater than 1. so we use g(x) = -2

g(4) = -2

ACCESS MORE